Virtual Simulators for Inclusive Teacher Training: Findings from the scientific literature - Andrade-Sánchez, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article shares the results of the bibliometric review process of indexed scientific literature on the use of virtual simulators and learning simulation in the training and qualification of the professional profile of teachers, related to the challenges of inclusive and intercultural education. This state of the art is configured as a structural input to continue with the research process that projects the design of a virtual simulator in inclusive didactic situations